Religious-Based Entrepreneurship Education to Build Student Independence Character in Islamic Boarding School - Moch Ibrahim; Mukhamad Ilyasin; Mursyid Mursyid (Tafkir: Interdisciplinary Journal of Islamic Education, 2026)
The independence of santri is one of the primary objectives of pesantren education; however, in practice, there remains a gap in the integration of entrepreneurship education with religious values, particularly within Islamic Religious Education (PAI). Entrepreneurship education is often understood in a pragmatic manner and has not been fully internalized as part of character formation grounded in Islamic teachings. Therefore, this study aims to examine in depth how religious-based entrepreneurship education is developed and implemented to shape the independent character of santri through the integration of Qur’anic values, the exemplary model of the Prophet Muhammad (peace be upon him), and the principles of sharia-based entrepreneurship. This study employed a qualitative method with a case study approach conducted at Pondok Pesantren Uswatun Hasanah Samarinda. Data were collected through in-depth interviews with pesantren leaders, teachers, and santri, observations of learning processes and entrepreneurial activities, and documentation of institutional programs and policies. The findings indicate that religious-based entrepreneurship education is developed through integrated intracurricular and extracurricular programs and implemented through classroom instruction combined with hands-on entrepreneurial practices. This integration of religious values and entrepreneurship has proven effective in fostering santri independence, encompassing independent thinking, mental attitudes, and financial self-reliance. The implications of this study highlight the importance of strengthening religious-based entrepreneurship education models as a strategic approach for pesantren in preparing santri who are independent, possess strong Islamic character, and are adaptive to contemporary socio-economic challenges.